Psychological Protection and Intervention Model for Child Victims of Sexual Violence at the Garut Prosecutor's Office - Helena Octavianne; Katarina Endang Sarwestri; Mia Amiati; Feza Reza; Donny Trianto (Fakultas Ilmu Sosial dan Ilmu Politik, Universitas Mulawarman, 2025)
Cases of sexual violence against children in Garut Regency are increasing year by year, indicating that more victims are daring to report despite facing psychological challenges and social stigma. This study aims to explore the psychological protection and intervention model applied in the investigation process at the Garut District Attorney's Office, with a focus on the Women, Children, and Disability Justice Post. The method used in this study is a descriptive qualitative approach with document analysis and media reporting. The results of the study show that the Justice Post has an important role in providing psychological support and access to justice for victims, by creating a safe space for victims to express individual experiences. However, there are still challenges related to the social stigma and fear to report faced by victims. The implications of this study show the importance of inter-institutional collaboration in providing holistic protection for victims of sexual violence, by paying attention to psychological, medical, and legal aspects in the victim recovery process.